ASSESSMENT OF ANTIBIOTIC STEWARDSHIP IN TERTIARY HEALTH CARE TEACHING MEDICAL INSTITUTION IN CENTRAL INDIA - NATH MANJUSHA; SHARMA DEEPAK; NATH SOM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study was to mitigate the impact of antimicrobial resistance and ensure continued access to effective treatments for bacterial infections. This study was undertaken to explore the hospital status of antibiotic prescription and evaluate the impact of antibiotic stewardship in clinical wards of tertiary health care settings. Methods: This is hospital-based observational prospective study carried out in a tertiary health care settings. All patients of either sex of any age who came in outpatient department and admitted in inpatient department of medicine, orthopedics, surgery, and pediatric departments and prescribed antibiotics were selected randomly in the study. Results: Study response rate was male predominance (57%). Empiric antimicrobials were mainly prescribed orally (47.3%), significantly higher than injectable route (22.8%) (p<0.001), while the majority were not given an empiric antibiotic by a clinical expert. A significantly high number of patients were prescribed injectable 1st Antimicrobial after surgery/culture, namely, injectable piperacillin+tazobactum (35.5%), followed by injectable cephalosporin (34.0%), amikacin injection/4.5%, and injection carbapenem/1.8% (p<0.001). Its frequency is significantly high with BD dose (66.8%) and the majority prescribed for period of 6–10 days (63.5%) followed by 1–6 days (19.5%) (p<0.001). Conclusion: As all prescriptions got optimal dose and duration of therapy, the stay of patients in the hospital was following Indian Council of Medical Research (2019) guideline therefore, it can thus be said that the results of this study revealed precise prescribing pattern of antibiotics. However, emphasis on information technology staff and patient education is vital in incorporating stewardship protocols. Emphasizing the importance of conducting antibiotic time-outs within 48–72 h is crucial for reassessing the necessity and choice of antibiotics. Such stewardship studies are instrumental in monitoring patterns of antibiotic usage and aid in future policy-making steps.